The effect of aroma stimulation during isotonic exercise on the rating of perceived exertion and blood fatigue factors of athletes with patellofemoral pain syndrome - Choo, JongHoo; Ju, Sungbum; Kim, Sangsoo (Journal of Physical Therapy Science, 2018)
[Purpose] The purpose of this study is to examine the effect of aroma stimulation during isotonic exercise on the rating of perceived exertion (RPE) and the blood fatigue factors of athletes who have patellofemoral pain syndrome (PFPS). [Subjects and Methods] The research subjects were seven athletes in their twenties who suffer from PFPS. They were divided into a control group and an aroma stimulation group and performed isotonic exercises repeatedly. After exercising, the RPE and blood fatigue factors, including creatine phosphokinase (CPK), lactate dehydrogenase (LDH), and ammonia, were measured through blood sampling. [Results] The aroma stimulus group showed significantly lower RPE than the control group immediately after exercising, which included leg presses, leg curls, bicep curls, and leg extensions. Among the blood fatigue factors, the change in LDH indicated the effect of aroma stimulation. [Conclusion] We confirmed that aroma stimulation during isotonic exercise has the positive effect of reducing the RPE and blood fatigue factors, such as blood LDH, of the athletes with PFPS.